2014
DOI: 10.9790/3021-04552834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic field on performance and emission of single cylinder four stroke diesel engine

Abstract: -To analyse experimental investigates on the Performance and Emission of Single Cylinder Four Stroke Diesel engine under the power of producingan effect of magnetic field. The magnetic field applied along the fuel line immediately before fuel injector. It has been reported that magnetic field helps to improved mixture formation by increasing the atomization process of the spray in the combustion chamber due to increasing the rate of disintegration of the droplets as a result of reduction in the surface tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 2 publications
1
23
1
2
Order By: Relevance
“…Contrary to this study, the CO 2 increased by 7% (Ugare et al, 2014) and 10% (Faris et al, 2012). Patel et al (2014) noted 30%, 27% and 9.72% reduction in HC, NO x and CO 2 , respectively, with effect of magnetic field.…”
Section: Impact Of Magnetic Tube On Energy Performancecontrasting
confidence: 46%
See 4 more Smart Citations
“…Contrary to this study, the CO 2 increased by 7% (Ugare et al, 2014) and 10% (Faris et al, 2012). Patel et al (2014) noted 30%, 27% and 9.72% reduction in HC, NO x and CO 2 , respectively, with effect of magnetic field.…”
Section: Impact Of Magnetic Tube On Energy Performancecontrasting
confidence: 46%
“…Habbo et al (2011) used 1000 and 2000 gauss magnets in a single cylinder four stroke engine and the specific fuel consumption reduced by 12.9 and 21.3% respectively. In their study, (Patel et al, 2014) reported a 2% increase in BTE when applying a 2000 gauss magnet, while Habbo et al (2011) showed 4% and 7.6% for 1000 and 2000 gauss magnetic fields in single cylinder four stroke engines.…”
Section: Impact Of Magnetic Tube On Energy Performancementioning
confidence: 99%
See 3 more Smart Citations